Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.29054/apmc/17.435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Amniotic Fluid Index in Maternal Oral Hydration Therapy with Routine Hydration in Third Trimester Oligohydramnios

Abstract: Objective: The objective of the study was to compare mean Amniotic Fluid Index (AFI) in maternal oral hydration with routine hydration in third trimester oligohydramnios. Study design: Randomized control trial. Settings: Department of Gynea/Obs Faisalabad Medical University, Faisalabad. Duration of study: 6 months from 1 st June to 30 th November 2016. Methodology: A total of 80 cases (40 in each group), were included in the study, Group A was oral hydration group and was enquired about daily water intake. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The results were comparable to a study conducted in Faisalabad Medical University, Faisalabad. 5 Our findings were also agreed with study conducted in Egypt, they show the good effect of oral hydration over IV hydration. 4 Gizzo et al observed that in isolated oligohydramnios maternal oral hydration is more effective than intravenous hydration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results were comparable to a study conducted in Faisalabad Medical University, Faisalabad. 5 Our findings were also agreed with study conducted in Egypt, they show the good effect of oral hydration over IV hydration. 4 Gizzo et al observed that in isolated oligohydramnios maternal oral hydration is more effective than intravenous hydration.…”
Section: Discussionsupporting
confidence: 92%
“…So maternal hydration is considered an effective and cheap intervention to treat oligohydramnios in resource poor setting like ours. 5 Maternal hydration increases the amniotic fluid through reduction in maternal plasma osmolality which result in increased AFI. The mother's fluid balance has great impact on amniotic fluid.…”
Section: Introductionmentioning
confidence: 99%